2020
DOI: 10.4236/health.2020.122017
|View full text |Cite
|
Sign up to set email alerts
|

Availability, Management and Use of Priority Life-Saving Medicines for Under-Five Children in Two Health Districts in Senegal: A Cross-Sectional Study

Abstract: Under-five mortality remains a major concern in the world and in Senegal. It is mainly due to preventable and treatable diseases with priority life-saving medicines for under-five children. This study evaluated the availability, management and use of these drugs in two health districts in Senegal. A descriptive cross-sectional study was conducted in the health districts of Guediawaye and Pete from 01 November 2018 to 31 January 2019. The health district of Guediawaye is in the region hosting the Senegalese cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…This finding shows that mothers, neonates, and children lost or endangered their life following the stock-out of some lifesaving drugs given that all hospitals placed at least one emergency order within a year. With its gaps, this study indicated a stock-out 59(75.64%) which is higher than the previous studies, 14 (61.30%), 27 54.3%, 29 and 74.3% 30 with a mean stock-out duration of 70.71 27 and 26 29 days. The new kaizen approach and enactment of Dagu 2.0 were the possible means for the availability of MNCH drugs over the previous studies.…”
Section: Discussioncontrasting
confidence: 80%
“…This finding shows that mothers, neonates, and children lost or endangered their life following the stock-out of some lifesaving drugs given that all hospitals placed at least one emergency order within a year. With its gaps, this study indicated a stock-out 59(75.64%) which is higher than the previous studies, 14 (61.30%), 27 54.3%, 29 and 74.3% 30 with a mean stock-out duration of 70.71 27 and 26 29 days. The new kaizen approach and enactment of Dagu 2.0 were the possible means for the availability of MNCH drugs over the previous studies.…”
Section: Discussioncontrasting
confidence: 80%
“…Seven other supplementary medicines were chosen to treat important national health problems and the burden of local diseases for children (such as pneumonia, diarrhoea, colds and pain). When developing the supplementary list, we referenced medicine lists from previous studies, [9][10][11][12][13][14][15][16][17][18][19][20] guidelines and documents (such as the NEML (2018), 23 the seventh WHO EMLc (2019), 24 the WHO's list of priority life-saving medicines for women and children (2012) 25 . The suitability of selected medicines was also checked through the results from a pilot test in a public health facility and a private drugstore in October 2020.…”
Section: Surveyed Medicinesmentioning
confidence: 99%
“…There are only few studies on EMs for children (cEMs). [9][10][11][12][13][14][15][16][17][18][19][20][21] Their results showed that low availability, high prices and poor affordability have kept cEMs out of reach.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of manipulated adult dosage forms can bring unwanted outcomes, treatment failure, and may go to the extent of losing the child. [7][8][9] most of published studies also suggested that better availabilities and rational utilizations antibiotic treatment and immunization can significantly reduces deaths. 10 Despite the introduction of priority medicines for children under five at the global level, research conducted in the Tigray region of Ethiopia demonstrated low availability of the medicines in public health facilities (The average availability of the most expensive drugs was in the range 0-4.5%, while the lowest-priced medicines were in the range 10.7-75%).…”
Section: Introductionmentioning
confidence: 99%